Diversification of piRNAs expressed in PGCs and somatic cells during embryonic gonadal development. Issue 9 (1st September 2020) - Barreñada, Odei; Fernández-Pérez, Daniel; Larriba, Eduardo; Brieño-Enriquez, Miguel; del Mazo, Jesús
ABSTRACT: piRNAs are small non-coding RNAs known to play a main role in defence against transposable elements in germ cells. However, other potential functions, such as biogenesis and differences in somatic and germline expression of these regulatory elements, are not yet fully unravelled. Here, we analysed a variety of piRNA sequences detected in mouse male and female primordial germ cells (PGCs) and gonadal somatic cells at crucial stages during embryonic differentiation of germ cells (11.5–13.5 days post-coitum). NGS of sncRNA and bioinformatic characterization of piRNAs from PGCs and somatic cells, in addition to piRNAs associated with TEs, indicated functional diversification in both cell types. Differences in the proportion of the diverse types of piRNAs are detected between somatic and germline during development. However, the global diversified patterns of piRNA expression are mainly shared between germ and somatic cells, we identified piRNAs related with molecules involved in ribosome components and translation pathway, including piRNAs derived from rRNA (34%), tRNA (10%) and snoRNA (8%). piRNAs from both tRNA and snoRNA are mainly derived from 3ʹ and 5ʹ end regions. These connections between piRNAs and rRNAs, tRNAs or snoRNAs suggest important functions of specialized piRNAs in translation regulation during this window of gonadal development.